Impact of COVID-19 on Online Gambling – A General Population Survey During the Pandemic - Håkansson, Anders (Frontiers in Psychology, 2020)
The COVID-19 pandemic may have severe impact on mental health, and concerns have been raised about potentially increased online behavior and possibly increased gambling problems, such as in sports bettors at risk of transfer to even riskier forms of gambling during sports lock-down. Given the need for objective data about gambling behavior during the pandemic, the present analysis, from a project assessing online gambling in Sweden, aimed to study past-30-day gambling patterns in online gamblers in Sweden. The study, carried out in May, 2020, during the pandemic and its restrictions on society, included past-year online gamblers (N=997). Past-30-day gambling for several gambling types was lower compared to a previous study in online gamblers in the same setting, while online non-sports gambling remained at high levels. Those reporting sports betting even during a period with decreased sports betting occasions proved to have markedly higher gambling problems. COVID-19 may alter gambling behaviors, and online gamblers who maintain or initiate gambling types theoretically reduced by the crisis may represent a group at particular risk.